Legitimacy and the recognition of creativity in organisations - Lamb, Rachael Claire (2019)
This thesis explores how legitimacy is enacted in an organisational setting during the recognition of creative ideas. Exploring how legitimacy is afforded to creative ideas in organisations is relevant and timely due to the increasing focus on creativity and innovation as a mechanism for competitive advantage, growth and profitability in the contemporary context of uncertainty, disruption and rapid change. Legitimacy integrates individual, group and institutional interests aligning desired outcomes within the organisation through effective decision making and consensus, without the explicit exertion of power. Although widely studied in the entrepreneurship and institutional literature as a mechanism to afford recognition and credibility, legitimacy has not been widely explored within the context of creativity and innovation. Consequently, it requires deeper examination within this context as the ability to identify and implement novel, appropriate and valuable ideas is of critical importance to organisations. The financial, operational and reputational cost of investing in a product or service which proves not to be viable is significant. To overlook or dismiss a potentially viable idea can incur an even heavier price if a competitor or new market entrant develops this idea gaining positive returns. Within the creativity literature, evidence regarding how ideas are recognised is growing. While the act of recognition is acknowledged as important, relatively little is known about the processes surrounding consensus upon what is, and what is not, creative thus, greater attention to examining legitimacy as an important factor in the recognition and selection of ideas is necessary. In addition, there are few empirical studies focused upon the recognition of creativity within an organisational setting which reflects the dominance of psychological perspectives, quantitative research and experimental studies at the expense of interpretive work. This thesis employs a social psychology approach to exploring legitimacy theory as part of the creative process. This allows a multi-level analysis of behaviour surrounding how creative ideas gather momentum, support and resource, drawing on ‎Amabile’s Componential Theory of Creativity (1983) and research into sources and objects of legitimacy (Dornbusch and Scott, 1975) and Acknowledged Legitimising Elements (ALEs) and Regime Legitimising Formulas (RLFs) (Zelditch and Walker, 1993, 2003). The research explores how employees at different levels within a large, technology multi-national corporate legitimise and privilege certain ideas, and individuals, rather than others. The exploration of creativity within a complex operational and commercial environment provides an opportunity to observe how socio-psychological factors influence what is recognised as legitimate and how legitimacy is enacted by management, together with employee responses to such processes. The central research question considered is: How does legitimacy theory account for creativity is recognised within an organisational setting? To address this question, the thesis adopts a qualitative case study approach to provide a bounded exploration of the topic centred on the use of an online Innovation Portal to seek ideas for complex, ill-defined challenges and opportunities across the entire organisation. The case enables the investigation of multiple examples of the phenomenon situated within one organisational context. Data were gathered over a period of six months drawing from 26 semi-structured interviews with senior managers and a range of employees from diverse positions, tenure and departments within the organisation. In addition, participant observation, grey media sources and informal interchanges were utilised. A thematic analysis identified prominent recurring themes and meanings surrounding the recognition of creativity. The findings point to three levels at which legitimacy operates on creativity: organisational; individual and social. Organisational level factors include aspects such as structure, regulation, culture, and hierarchy, convey validity (collective legitimacy) on the status quo. These factors reproduce existing conditions surrounding creativity. Individual level factors such as motivation and conformity, influence the degree of propriety (individual legitimacy) afforded to social norms. These factors enable or constrain creative response. Social level factors such as social capital and social networks are the mechanism by which people seek to have their ideas legitimated (through authorisation of superiors and endorsement by peers). These factors ameliorate organisational factors through individual agency. The research findings suggest organisational emphasis on operational and financial objectives conveys legitimacy on those ideas which are considered apposite to achieve these goals. Individuals with management and commercial responsibility within the organisation reflect and enact this through the tendency to privilege appropriateness for that context over novelty. Individuals with product, service or process responsibility are more likely to promote novelty over appropriateness in response to calls for creative ideas, thus conflicting with the organisational and managerial view. Employees who pursue novel creative ideas in an attempt to attain legitimacy do so against organisational norms, therefore considerable individual action and social interaction is necessary to overcome organisational inertia. This creates a paradox where the organisation articulates the need for radical and disruptive creativity and innovation while simultaneously rejecting those creative ideas which are highly novel. The main contribution of the thesis is to our understanding of the recognition of creativity as a ‘re-cognition’; where managers who judge creativity already have their perception of who and what is creative framed by the validity and propriety of organisational norms. This provides a more nuanced perspective on how individual and collective understanding of what is considered legitimate in the organisation influences the recognition of who and what is considered creative. Three further theoretical contributions are evident; first, it questions current assumptions about the self-evident nature of judgements surrounding the recognition of creativity; second, it highlights the role individual non-conformity plays in both the managerial and product/service populations in pursuing creative ideas outside of the legitimated norm. Third, it yields insight into the mediating effects which social strategies have on the enactment and legitimisation of creative ideas by individuals in an organisational setting. This thesis illuminates management and employee practices surrounding the recognition of creative ideas and provides a further explanatory mechanism for how and why organisations desire creativity in principle but may be biased against it in practice. Consequently, the thesis aims to contribute to discussions surrounding how the recognition of creativity can be better understood to benefit organisations and the wider communities they serve.